2019
DOI: 10.1007/s10802-019-00594-7
|View full text |Cite
|
Sign up to set email alerts
|

Children with Behavioural Problems Misinterpret the Emotions and Intentions of Others

Abstract: Research indicates that the misinterpretation of other's emotions or intentions may lead to antisocial behaviour. This study investigated emotion and intention recognition in children with behavioural problems and examined their relationship and relations with behaviour problem severity. Participants were 7-11 year old children with behavioural problems (n = 93, mean age: 8.78, 82.8% male) who were taking part in an early intervention program and typically developing controls (n = 44, mean age: 9.82, 79.5% mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
3
8
0
Order By: Relevance
“…With the gradual deepening of society and continuous contact with the environment, children’s physical and mental development problems gradually increased [ 1 , 2 , 3 ]. In the health field of China’s “Learning and Development Guide for Children Aged 3–6”, it is suggested that parents and teachers help children learn to express and adjust their emotions correctly, and give appropriate guidance so that children can express their emotions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the gradual deepening of society and continuous contact with the environment, children’s physical and mental development problems gradually increased [ 1 , 2 , 3 ]. In the health field of China’s “Learning and Development Guide for Children Aged 3–6”, it is suggested that parents and teachers help children learn to express and adjust their emotions correctly, and give appropriate guidance so that children can express their emotions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aside from externalizing symptoms, these children had also experienced severe mood problems. These might have impaired their cognitive processes and emotional and mentalizing skills, and challenged their ability to position themselves as an observer both of their own and of others’ actions (Shirk, 1988; Spivack & Shure, 1982; Wells et al, 2020). However, we found that the children participated in these post‐therapy research interviews as dialogical partners, talking in a reflective, open, and emotional way.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, deficiencies in strategies for making and keeping friends, unawareness of the possible consequences of one's action, and not perceiving how others feel are among the difficulties that generate stress and strains in social situations and impede the achievement of socially satisfying goals (Hill & Maughan, 2001; Kazdin, 2005; Shirk, 1988; Spivack & Shure, 1982). A recent study by Wells et al, (2020) showed that the ability to identify others’ emotions and intentions is impaired in children with behavioral problems. These social cognitive processes were found to be related and inversely associated with the severity of behavioral problems.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, several attempts have been made to summarise the effectiveness of AAT in children and adults, including children with autism spectrum disorder (Fung & Leung, 2014), adults with autism spectrum disorder (Wijker et al, 2021), children with pervasive developmental disorder (Martin and Farnum, 2002), children with Down syndrome (Griffioen et al, 2019), children who were sexually abused (Dietz et al, 2012) and children with attention-deficit hyperactivity disorder (Juríčková, et al, 2020). Beetz et al (2021) categorised the outcomes of DAT as (1) improvements in social skills such as empathy and communication (Hill et al, 2019a(Hill et al, , 2019bStevenson et al, 2015;Wells et al, 2019), (2) psychological effects such as improvements in concentration and motivation (Busch et al, 2016;Hill et al, 2019aHill et al, , 2019bSchuck et al, 2013Schuck et al, , 2018 and (3) neurobiological effects such as decreases in heart rate and blood pressure (Nagasawa et al, 2015). While most studies on AAT focussed on the effectiveness of dogassisted therapy (DAT), studies systematically investigating the therapy approaches, settings and research methodology are scarce (Fine et al, 2019).…”
mentioning
confidence: 99%